Constructing Musical Heritage in Action: The Case of Wilamowice - Małanicz-Przybylska, Maria (Interdisciplinary Studies in Musicology, 2022)
Wilamowice, a small town in southwest Poland, is unique in many ways. It was settled in the 13th century by German tribes, and it preserved its distinct culture for a long time. The inhabitants of Wilamowice spoke their own language, wore original costumes, and observed local customs. Due to their merchants’ skills, they were gradually becoming a wealthy community, which resulted in the most prosperous years of the town and its culture starting from the beginning of the 19th century. The situation changed in the middle of the 20th century. As a result of the dramatic war and post-war circumstances, the culture of Wilamowice began to disappear. Nowadays, thanks to the work of local activists and scholars, intensive revitalisation of the Vilamovian language and costumes has begun. This process had already been described in various writings (Król, 2016, Wicherkiewicz, 2003), but Vilamovian music culture remained almost completely unexplored. I decided to fill in this blind spot, and in 2016 began my fieldwork research on traditional music and dances in Wilamowice. At the beginning of my research, I realised that the task wasn’t easy, as there remained only a few archive materials concerning Vilamovian music (Horak, 1960, Horak, 1981). Thus, the primary materials I could use in my research were ethnographic interviews and observations. On this basis, I aimed to reconstruct the forgotten soundscape of Wilamowice. But, what was more important for me, I tried to describe modern contexts in which music is used by the local community as a part of the process of constructing their identity and heritage. The essential question of my text is: ‘What kind of music can be called Vilamovian, how do modern people use it and what for?’.